Yoga exercise for endurance improvement in coronary heart disease patients: a case study - Ariyanto, Heri; Ayunitias, Imelda; Patima, Patima; Jamaludin, Thandar Soe Sumaiyah; Che Hasan, Muhammad Kamil; Nik Mohd Hatta, Nik Noor Kaussar; Shahadan, Siti Zuhaidah; Nurumal, Mohd. Said (IIUM Press, 2025)
Background: Coronary heart disease (CHD) is a leading cause of death, particularly in developing countries. It is characterized by the narrowing of coronary blood vessels, which restricts blood flow to the heart, leading to symptoms such as shortness of breath and reduced endurance. This study aims to explore the effectiveness of yoga exercise in improving endurance and reducing shortness of breath in patients with CHD. Methods: A descriptive case study approach was utilized. A 61-year-old female patient with CHD participated in yoga and breathing exercises over a period of 16 weeks. Yoga was performed 2-3 times a week for 20-30 minutes, while breathing exercises were incorporated regularly. The Borg scale was used to assess breathlessness, and endurance was measured using the Six-Minute Walk Test (6MWT). Results: After 16 weeks, the patient's Borg scale score decreased from 3 to 0.5, indicating a reduction in shortness of breath. Additionally, her endurance improved significantly, with the metabolic equivalents (METs) value increasing from 1.6 to 3.35. These results demonstrate substantial improvements in physical capacity and a reduction in breathlessness symptoms following yoga and breathing exercises. Conclusion: This study suggests that yoga exercises, combined with breathing exercises, can be an effective adjunct to traditional cardiac rehabilitation, improving both endurance and symptoms of breathlessness in CHD patients. Further research with larger sample sizes and longer durations is recommended to confirm these findings and explore the long-term benefits of yoga for cardiovascular health.